The account of sagging of wires at definition of specific potential factors of air High-Voltage Power Transmission Lines - Suslov V.M. (Problems of the Regional Energetics)
The opportunity approached is shown, but more exact as it is usually accepted, the account of sagging of wires at definition of specific potential factors air High-Voltage Power Transmission Lines. The technique of reception of analytical expressions is resulted. For an opportunity of comparison traditional expressions for specific potential factors are resulted also. Communication of the offered and traditional analytical expressions is shown. Offered analytical expressions are not difficult for programming on a personal computer of any class and besides they allow to make an estimation of an error of traditional expressions by means of parallel definition of specific potential factors by both ways.